Moodle for Mobile Learning. - Aberdour, Mark (Packt Publishing, 2013)
A guide with practical examples that gives you hands-on knowledge in creating learning environments for Mobile devices using Moodle, while also empowering you to create your own effective mlearning course designs.""Moodle for Mobile Learning"" is primarily aimed at Moodle course practitioners - teachers, tutors, instructors, and learning and development professionals. It does not require you to have an in-depth knowledge about any mobile technologies. It is for anyone who has the desire to deliver great courses that allow their learners to interact using the devices in their pockets.